Measuring Public Pension Liabilities in the European Union - Olaf Weddige (Peter Lang International Academic Publishers, 2011)
Due to the demographic development, public pension systems in the European Union organized on a pay-as-you-go (PAYG) principle will be forced to either raise contribution rates or taxes, shorten future replacement rates, or enforce a combination of both. In this regard, two important issues have to be addressed: The first issue refers to the question of measuring the public pension liabilities of private households until today. The extent of these liabilities has an impact on the saving behaviour. The second issue refers to the consequences of the demographic development for future retirees and contributors and examines the sustainability of pension schemes by confronting the present value of future pension payments with the present value of future contributions.
Keywords: 330